A ferroelectric nematic liquid crystal molecule and its application
By optimizing the structure of liquid crystal molecules and introducing polar groups, breaking through the limitation of symmetry and achieving ferroelectricity, the problems of narrow phase transition temperature and poor stability of traditional ferroelectric liquid crystal materials have been solved, and high spontaneous polarization strength and widespread application have been obtained. Foreground ferroelectric nematic liquid crystal molecules.
Patent Information
- Application Number
- CN202411523622.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Traditional ferroelectric liquid crystal materials have narrow phase transition temperature range, poor room temperature stability, and it is difficult for traditional liquid crystal molecules to achieve ferroelectricity due to limited symmetry.
A ferroelectric nematic liquid crystal molecule is adopted, with structural formulas of ETA094 and ETB095. By optimizing the molecular structure and introducing polar groups, it breaks through the symmetry limitations of traditional liquid crystal molecules and realizes ferroelectricity.
The liquid crystal molecules achieve phase change in an ultra-wide temperature range of -100°C to 250°C, have high spontaneous polarization intensity, improve the dielectric constant and electric field response speed, and are suitable for high-performance optoelectronic devices.
Smart Images

Figure CN119040008B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of optoelectronic materials, and in particular to a ferroelectric nematic liquid crystal molecule and an application thereof. Background Art
[0002] Liquid crystal is a special state of matter between liquid and solid, with both the fluidity of liquid and the anisotropy of crystal. The arrangement of liquid crystal molecules is highly ordered and highly sensitive to external energy (such as electric field, magnetic field and thermal energy). When affected by these external factors, the arrangement of liquid crystal molecules will change, causing significant changes in their physical properties, especially optical properties. Based on these unique physical and optical properties, liquid crystal materials are widely used in high-tech fields such as communications, liquid crystal display units, and nonlinear optical elements. However, traditional liquid crystal materials are usually non-polar fluids and do not have polarization characteristics, which limits the development of core technical indicators such as dielectric constant and electric field response speed in the optoelectronic field. With the advancement of science and technology and the continuous improvement of human living standards, the performance requirements for optoelectronic materials are getting higher and higher, especially in terms of improving dielectric constant and response speed. Research and development of new liquid crystal devices has always been the focus of common concern in academia and industry.
[0003] In recent years, the performance of liquid crystal materials has been significantly improved by introducing ferroelectricity. Ferroelectricity refers to the fact that in some crystals, due to the misalignment of the centers of positive and negative charges, an electric dipole moment is formed, and under the action of an external electric field, the direction of the electric dipole moment changes. This phenomenon makes ferroelectric liquid crystal materials not only have the orderliness and fluidity of liquid crystals, but also have unique characteristics such as spontaneous polarization. Compared with traditional non-polar liquid crystal materials, this ferroelectric liquid crystal material has a higher dielectric constant, response speed and stronger photoelectric effect. Therefore, ferroelectric liquid crystals show unique advantages and broad application prospects in the field of optoelectronic materials. Traditional liquid crystal molecules are difficult to achieve ferroelectricity due to symmetry restrictions. Therefore, although ferroelectric liquid crystal materials show many excellent properties, the current research and application of such materials is still limited. Traditional ferroelectric liquid crystal materials usually have problems such as a narrow phase transition temperature range and poor stability at room temperature, which limits their feasibility in practical applications. Therefore, the development of ferroelectric liquid crystal materials with good room temperature stability and a wide phase transition temperature has become an important research direction in the field of optoelectronic materials.
[0004] In 1966, scientists discovered that a "V"-type liquid crystal molecule can exhibit ferroelectricity. This "V"-type molecule breaks through the limitations of the symmetrical structure of traditional liquid crystal molecules. Although it does not contain chirality itself, it exhibits unique supramolecular chiral behavior. This molecular structure gives it ferroelectricity and unique optoelectronic properties. Compared with traditional rod-shaped liquid crystal molecules, "V"-type liquid crystal molecules not only have a simple synthesis process and readily available raw materials, but also can enhance the interaction between molecules by connecting different polar groups, thereby maintaining the orientation order of the molecules and improving their fluidity, dielectric constant and nonlinear optical response and other properties. By optimizing the molecular structure of the "V"-type liquid crystal molecules and introducing polar groups, the optoelectronic properties of the liquid crystal material are further improved, making it show extremely high application potential in the field of optoelectronic devices. Summary of the invention
[0005] In order to solve the problems of narrow phase transition temperature range, poor room temperature stability and difficulty in achieving ferroelectricity of conventional liquid crystal molecules due to symmetry limitations in the prior art ferroelectric liquid crystal materials, the present invention proposes a preparation method and application of ferroelectric nematic liquid crystal molecules. The technical solution of the present invention is as follows:
[0006] A ferroelectric nematic liquid crystal molecule, the structural formula of which is one of the following structural formulas ETA094 and ETB095:
[0007]
[0008] ETA094;
[0009]
[0010] ETB095.
[0011] The invention discloses an application of ferroelectric nematic liquid crystal molecules in optoelectronic devices, including communication equipment, liquid crystal display units and nonlinear optical elements.
[0012] Compared with the prior art, the present invention solves the problems of narrow phase transition temperature range, poor room temperature stability and difficulty in achieving ferroelectricity of traditional liquid crystal molecules due to symmetry limitations in the prior art ferroelectric liquid crystal materials. The specific beneficial effects are as follows:
[0013] 1. Ultra-wide phase change temperature range: The liquid crystal molecules can achieve phase change within an ultra-wide temperature range of -100°C to 250°C, which expands the applicable temperature range of the material and can work stably in extreme environments, making it suitable for optoelectronic application scenarios with strict temperature requirements.
[0014] 2. High spontaneous polarization intensity: The liquid crystal material has a high spontaneous polarization intensity, which enhances its electrical properties. High spontaneous polarization helps to improve the material's electric field response speed and dielectric constant, making it outstanding in high-speed electro-optical modulation and efficient photoelectric conversion.
[0015] 3. Excellent performance of ferroelectric liquid crystal: Combining ferroelectricity and liquid crystal properties, the molecules have the advantages of ferroelectric spontaneous polarization and high dielectric constant while maintaining the high fluidity of liquid crystal, effectively overcoming the shortcomings of traditional liquid crystal materials.
[0016] 4. Wide application fields: The ferroelectric liquid crystal molecular material can be widely used in communication equipment, liquid crystal display units and nonlinear optical elements, showing its broad application prospects in the field of optoelectronic materials and meeting the needs of future optoelectronic devices for high-performance materials.
[0017] 5. Breaking through the symmetry limitations of traditional liquid crystal molecules: Due to its "V"-shaped molecular structure, it breaks through the symmetry limitations of traditional rod-shaped liquid crystal molecules and achieves ferroelectricity, making liquid crystal materials more flexible in the preparation process and having higher design plasticity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The synthetic route of ferroelectric nematic liquid crystal molecules ETA094 and ETB095;
[0019] Figure 2 is the intermediate 1 described in Example 1 1 H-NMR spectrum;
[0020] Figure 3 is the intermediate 1 described in Example 1 13 C-NMR spectrum;
[0021] Figure 4 is the intermediate 2 described in Example 1 1 H-NMR spectrum;
[0022] Figure 5 is the intermediate 2 described in Example 1 13 C-NMR spectrum;
[0023] Figure 6 is the intermediate 3 described in Example 1 1 H-NMR spectrum;
[0024] Figure 7 is the intermediate 3 described in Example 1 13 C-NMR spectrum;
[0025] Figure 8 is the intermediate 4 described in Example 1 1 H-NMR spectrum;
[0026] Fig. 9 is the intermediate 4 described in Example 1 13 C-NMR spectrum;
[0027] Fig.10 is the intermediate 5 described in Example 1 1 H-NMR spectrum;
[0028] Fig.11 is the intermediate 5 described in Example 1 13 C-NMR spectrum;
[0029] Fig.12 is the ferroelectric nematic liquid crystal molecule ETA094 described in Example 1 1 H-NMR spectrum;
[0030] Fig.13 is the ferroelectric nematic liquid crystal molecule ETA094 described in Example 1 13 C-NMR spectrum;
[0031] Fig.14 is the intermediate 6 described in Example 2 1 H-NMR spectrum;
[0032] Fig.15 is the intermediate 6 described in Example 2 13 C-NMR spectrum;
[0033] Fig.16 is the intermediate 7 described in Example 2 1 H-NMR spectrum;
[0034] Fig.17 is the intermediate 7 described in Example 2 13 C-NMR spectrum;
[0035] Fig.18 is the ferroelectric nematic liquid crystal molecule ETB095 described in Example 2 1 H-NMR spectrum;
[0036] Fig.19 is the ferroelectric nematic liquid crystal molecule ETB095 described in Example 2 13 C-NMR spectrum;
[0037] Fig. 20 is a differential scanning calorimetry curve of the ferroelectric nematic liquid crystal molecule ETA094;
[0038] Fig.21 is a differential scanning calorimetry curve of the ferroelectric nematic liquid crystal molecule ETB095;
[0039] Fig. 22 This is the hysteresis loop diagram of the ferroelectric nematic liquid crystal molecule ETA094 at 150°C;
[0040] Fig.23 This is the hysteresis loop diagram of the ferroelectric nematic liquid crystal molecule ETB095 at 150°C;
[0041] Fig.24 The second harmonic nonlinear optical signal intensity diagram of ferroelectric nematic liquid crystal molecules ETA094 and ETB095 in different temperature regions;
[0042] Fig.25 Thermogravimetric analysis diagrams of ferroelectric nematic liquid crystal molecules ETA094 and ETB095. DETAILED DESCRIPTION
[0043] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0044] Example 1.
[0045] The preparation process of ferroelectric nematic liquid crystal molecule ETA094 includes the following steps:
[0046] S1: Synthesis of Intermediate 1
[0047] 80 ml of dimethyl sulfoxide was added to a three-necked flask, followed by 4-iodobenzaldehyde (10 g, 43.1 mmol, 1 equivalent), copper acetate monohydrate (6.2 mg, 3.1 mmol, 0.072 equivalent) and tert-butyl hydroperoxide (TBHP, 15.54 g, 172.4 mmol, 4 equivalent, 70% aqueous solution), and then p-benzoquinone (6.99 g, 64.65 mmol, 1.5 equivalent) was added, and the temperature was raised to 150°C for overnight reaction. After the reaction was completed, the system was cooled to room temperature, 200 ml of water was added to the system, and then extracted with ethyl acetate. Anhydrous sodium sulfate was added to the organic phase, and the crude product was obtained by drying, filtering, and evaporating the solvent under reduced pressure. The crude product was purified by column chromatography, and ethyl acetate: n-hexane = 1:5 was selected as the eluent for column chromatography purification to obtain a white solid, which was intermediate 1, with a yield of 62.6%. The structural formula of intermediate 1 is as follows:
[0048]
[0049] NMR characterization results:
[0050] The hydrogen spectrum is shown in Figure 2 As shown, the results are as follows: 1H NMR (500 MHz, DMSO) δ 9.56 (s, 1H), 8.14 (m, 2H), 7.74 (m, 2H), 7.25 (m, 2H), 6.87 (m, 2H);
[0051] Carbon spectrum Figure 3 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 167.17, 156.55,144.82, 137.56, 130.73, 130.49, 122.00, 1115.69, 93.16;
[0052] Mass spectrometry characterization results:
[0053] ESI (m / z): [M+H] + Calcd. for C 13 H9IO3,339.96; found, 340.92.
[0054] S2: Synthesis of Intermediate 2
[0055] 25 ml of N,N-dimethylformamide was added to a three-necked flask, and bromobutane (3.63 g, 26.46 mmol, 1 equivalent), potassium carbonate (7.31 g, 52.92 mmol, 2 equivalents) and intermediate 1 prepared by S1 in Example 1 (9 g, 26.46 mmol, 1 equivalent) were added thereto, and the reaction was continued at 80°C overnight; after the reaction was completed, the system was cooled to room temperature, 100 ml of water was added to the system, and then extracted with ethyl acetate, washed with water three times, and anhydrous sodium sulfate was added to the organic phase, and the crude product was obtained by drying, filtering, and evaporating the solvent under reduced pressure. Petroleum ether was added to the crude product, and the product was slurried at low temperature for 0.5 hours in an ethanol dry ice bath, filtered, and rinsed with petroleum ether to obtain a light yellow solid, which was intermediate 2, with a yield of 76%. The structural formula of intermediate 2 is as follows:
[0056]
[0057] NMR characterization results:
[0058] The hydrogen spectrum is shown in Figure 4 As shown, the results are as follows: 1 H NMR (500 MHz, DMSO) δ8.20(m, 2H), 7.78(m,2H), 7.28 (m, 2H), 7.01(m, 2H), 4.00 (d, 2H), 1.74 (p, 2H), 1.53 (h, 2H), 0.98 (t, 3H);
[0059] Carbon spectrum Figure 5 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.35, 156.53,144.82, 136.98, 130.58, 125.57, 122.49, 117.22, 100.34, 67.81, 31.13, 19.20,13.78;
[0060] Mass spectrometry characterization results:
[0061] ESI (m / z): [M+H] + Calcd. for C 17 H 17 IO3,396.02; found, 397.00.
[0062] S3: Synthesis of Intermediate 3
[0063] 35 ml of dioxane was added to a three-necked flask, and intermediate 2 (7.8 g, 19.69 mmol, 1 equivalent) prepared by S2 in Example 1, 3-bromophenylboronic acid (4.74 g, 23.62 mmol, 1.2 equivalent), and 2 mol / L sodium carbonate aqueous solution (39.4 ml, 78.74 mmol, 4 equivalent) were added thereto; under nitrogen protection, tetrakis(triphenylphosphine)palladium (0.45 mg, 0.4 mmol, 0.02 equivalent) was added to the mixed solution, and the temperature was raised to reflux for reaction for 8 hours. After the reaction is completed, the reaction mixture is cooled to room temperature, filtered with diatomaceous earth, the filter cake is rinsed with ethyl acetate, the filtrate is washed with water three times, anhydrous sodium sulfate is added to the organic phase, and the crude product is obtained by drying, filtering, and evaporating the solvent under reduced pressure; the crude product is slurried with petroleum ether and dichloromethane for 2 hours under low temperature conditions, wherein the ratio of petroleum ether to dichloromethane is 80:1, and then filtered, and the filter cake is rinsed with a small amount of petroleum ether to obtain a white solid, which is intermediate 3, with a yield of 55%. The structural formula of intermediate 3 is as follows:
[0064]
[0065] NMR characterization results:
[0066] The hydrogen spectrum is shown in Figure 6 As shown, the results are as follows: 1H NMR (500 MHz, DMSO) δ 8.20 (m, 2H), 7.90(m, 2H), 7.68 (s, 1H), 7.64 (s, 1H), 7.55 (s, 1H), 7.43 (s, 1H), 7.15(m, 2H),6.96 (m, 2H), 3.98 (s, 2H), 1.76 (s, 2H), 1.48 (s, 2H), 1.03 (s, 3H);
[0067] Carbon spectrum Figure 7 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.95, 156.53,144.82, 143.44, 139.18, 131.51, 130.91, 130.50, 127.78, 127.01, 126.39,123.41, 122.64, 116.86, 67.81, 31.13, 19.20, 13.78;
[0068] Mass spectrometry characterization results:
[0069] ESI (m / z): [M+H] + Calcd. for C 23 H 21 BrO3,424.07; found, 425.05.
[0070] S4: Synthesis of intermediate 4
[0071] Add 50 ml of anhydrous dichloromethane into a three-necked flask, add 4-bromophenol (10 g, 57.8 mmol, 1 eq), p-cyanobenzoic acid (10.28 g, 69.36 mmol, 1.2 eq) and N,N'-dicyclohexylcarbodiimide (DCC, 21.47 g, 104.04 mmol, 1.8 eq), then put it in an ice bath, under nitrogen protection, continue to add 4-dimethylaminopyridine (DMAP, 0.56 g, 4.62 mmol, 0.08 eq) dissolved in dichloromethane, react in an ice bath for 1 hour, then return to room temperature and react overnight. After the reaction is completed, the reaction system is added to a saturated sodium chloride aqueous solution, extracted with dichloromethane three times, and then anhydrous sodium sulfate is added to the organic phase to obtain a crude product by drying, filtering, and evaporating the solvent under reduced pressure; the crude product is purified by column chromatography, and petroleum ether and dichloromethane are selected as eluents, wherein the ratio of petroleum ether to dichloromethane is 1:1, and finally a yellow solid is obtained, which is intermediate 4, and the yield is 78.8%. The structural formula of intermediate 4 is as follows:
[0072]
[0073] NMR characterization results:
[0074] The hydrogen spectrum is shown in Figure 8 As shown, the results are as follows: 1 H NMR (500 MHz, DMSO) δ 8.41 (m, 2H), 8.10 (m, 2H), 7.65 (m, 2H), 7.29 (m, 2H);
[0075] Carbon spectrum Fig. 9 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.95, 150.17,132.82, 132.71, 132.33, 130.49, 124.18, 117.55, 117.28, 116.03;
[0076] Mass spectrometry characterization results:
[0077] ESI (m / z): [M+H] + Calcd. for C 14 H8BrNO2, 300.97; found, 301.95.
[0078] S5: Synthesis of Intermediate 5
[0079] 50 ml of tetrahydrofuran was added to a three-necked flask, and the intermediate 4 (13 g, 43.03 mmol, 1 equivalent) prepared by S4 in Example 1 was added thereto and dissolved. After cooling to -78°C, 2 mol / L n-butyl lithium (5 ml) solution was dripped into the system within 5 minutes, and stirred for 1 hour. Then, diboric acid pinacol ester (13.1 g, 51.63 mmol, 1.2 equivalent) was added to the system, and the reaction was allowed to proceed overnight after returning to room temperature. After the reaction was completed, 2 mol / L hydrochloric acid (HCl) was added to the system until the pH value of the solution was 2-3, and then extracted with ether, and anhydrous sodium sulfate was added to the organic phase. The light yellow solid was obtained by drying, filtering, and evaporating the solvent under reduced pressure, which was the intermediate 5 with a yield of 66%. The structural formula of the intermediate 5 is as follows:
[0080]
[0081] NMR characterization results:
[0082] The hydrogen spectrum is shown in Fig.10 As shown, the results are as follows: 1H NMR (500 MHz, DMSO) δ 8.20 (m, 2H), 7.91 (m, 2H), 7.76 (m, 2H), 7.10 (m, 2H), 1.23 (s, 12H);
[0083] Carbon spectrum Fig.11 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.95, 151.53,133.15, 132.82, 132.33, 130.49, 129.89, 118.35, 117.55, 116.03, 84.18, 24.88;
[0084] Mass spectrometry characterization results:
[0085] ESI (m / z): [M+H] + Calcd. for C 20 H 20 BNO4,349.15; found, 350.11.
[0086] S6: Synthesis method of ferroelectric nematic liquid crystal molecule ETA094
[0087] 100 ml of toluene and 10 ml of methanol were added to a three-necked flask, and intermediate 5 (3 g, 8.59 mmol, 1 equivalent) prepared by S5 in Example 1, intermediate 3 (4.02 g, 9.45 mmol, 1.1 equivalent) prepared by S3 and potassium acetate (1.01 g, 10.31 mmol, 1.2 equivalent) were added thereto; under nitrogen protection, tetrakis(triphenylphosphine)palladium (0.2 g, 0.17 mmol, 0.02 equivalent) was added continuously. After the feeding was completed, the reaction flask was transferred to a preheated oil bath pot and reacted at 110°C for 4 hours. After the reaction was completed, the reaction solution was poured into water, extracted with toluene, the organic phase was washed with water three times, anhydrous sodium sulfate was added to the organic phase, and the crude product was obtained after drying, filtering, and evaporating the solvent under reduced pressure. The crude product was purified by column chromatography, and ethyl acetate and n-hexane were selected as eluents, wherein the ratio of ethyl acetate to n-hexane was 1:9, and finally a light yellow solid was obtained, which was the ferroelectric nematic liquid crystal molecule ETA094, with a yield of 42%. The structural formula of the ferroelectric nematic liquid crystal molecule ETA094 is as follows:
[0088]
[0089] NMR characterization results:
[0090] The hydrogen spectrum is shown in Fig.12 As shown, the results are as follows:1 H NMR (500 MHz, DMSO) δ 8.40 (m, 2H), 8.13(m, 3H), 7.89(m, 2H), 7.80 (m, 2H), 7.79(m, 2H), 7.68(m, 3H), 7.25(m, 2H),7.16 (m, 2H), 6.95(m, 2H), 3.96 (s, 2H), 1.75 (s, 2H), 1.48 (s, 2H), 1.03 (s, 3H);
[0091] Carbon spectrum Fig.13 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 165.05, 164.95,156.53, 150.11, 144.82, 142.92, 142.42, 139.36, 134.12, 132.82, 132.33,130.50, 130.11, 127.78, 127.71, 127.01, 125.81, 125.71, 125.61, 122.64,121.98, 117.55, 116.86, 116.03, 67.81, 31.13, 19.20, 13.78;
[0092] Mass spectrometry characterization results:
[0093] ESI (m / z): [M+H] + Calcd. for C 37 H 29 NO5,567.20;found, 568.12.
[0094] Example 2.
[0095] The preparation process of ferroelectric nematic liquid crystal molecule ETB095 includes the following steps:
[0096] S1: Synthesis of intermediate 6
[0097] Anhydrous dichloromethane was added to a three-necked flask, and 4-bromophenol (10 g, 57.8 mmol, 1 equivalent), 4-nitrobenzoic acid (12 g, 69.36 mmol, 1.2 equivalent), and DCC (21.47 g, 104.04 mmol, 1.8 equivalent) were added thereto, and an ice bath was conducted. Under nitrogen protection, DMAP (0.57 g, 4.62 mmol, 0.08 equivalent) dissolved in dichloromethane was continuously added, and the mixture was reacted in an ice bath for 1 hour, and then the mixture was returned to room temperature and reacted overnight. After the reaction was completed, the reaction system was added to a saturated sodium chloride aqueous solution, and after extraction with dichloromethane three times, anhydrous sodium sulfate was added to the organic phase, and the crude product was obtained by drying, filtering, and evaporating the solvent under reduced pressure. The crude product was purified by column chromatography, and petroleum ether and dichloromethane were selected as eluents, wherein the ratio of petroleum ether to dichloromethane was 1:1.5, and finally a yellow solid was obtained, namely intermediate 6, with a yield of 72.3%. The structural formula of intermediate 6 is as follows:
[0098]
[0099] NMR characterization results:
[0100] The hydrogen spectrum is shown in Fig.14 As shown, the results are as follows: 1 H NMR (500 MHz, DMSO) δ 8.40 (m, 2H), 8.19 (m, 2H), 7.64 (m, 2H), 7.25 (m, 2H);
[0101] Carbon spectrum Fig.15 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.95, 150.34, 150.17, 133.83, 132.71, 131.39, 124.18, 123.57, 117.28;
[0102] Mass spectrometry characterization results:
[0103] ESI (m / z): [M+H] + Calcd. for C 13 H8BrNO4, 320.96; found, 321.91.
[0104] S2: Synthesis of intermediate 7
[0105] In a three-necked flask, the intermediate 6 (14.8 g, 45.95 mmol, 1 equivalent) prepared by S1 in Example 2 was dissolved in ultra-dry tetrahydrofuran (60 ml), cooled to -78°C, and 2 mol / L n-butyl lithium (5 ml) solution was dripped into the system within 5 minutes. After stirring for 1 hour, the system was added with biboric acid pinacol (14 g, 55.14 mmol, 1.2 equivalents), and the reaction was restored to room temperature overnight. After the reaction, 2 mol / L HCl was added to the system to treat the pH value to 2-3, extracted with ether, dried the organic phase with anhydrous sodium sulfate and then filtered, and the organic phase was spin-dried to obtain a light yellow solid, which was intermediate 7, with a yield of 58%. The structural formula of intermediate 7 is as follows:
[0106]
[0107] NMR characterization results:
[0108] The hydrogen spectrum is shown in Fig.16 As shown, the results are as follows: 1 H NMR (500 MHz, DMSO) δ 8.42(m, 4H), 7.80(m, 2H), 7.23(m, 2H), 1.28(s, 12H);
[0109] Carbon spectrum Fig.17 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 164.95, 151.53,150.34, 133.83, 133.15, 131.39, 129.89, 123.57, 118.35, 84.18, 24.88;
[0110] Mass spectrometry characterization results:
[0111] ESI (m / z): [M+H] + Calcd. for C 19 H 20 BNO6,369.14; found, 370.11.
[0112] S3: Synthesis method of ferroelectric nematic liquid crystal molecule ETB095
[0113] 100 ml of toluene and 10 ml of methanol were added to a three-necked flask, and intermediate 7 (3.5 g, 9.48 mmol, 1 equivalent) prepared by S2 in Example 2, intermediate 3 (4.44 g, 10.43 mmol, 1.1 equivalent) prepared by S3 in Example 1 and potassium acetate (1.12 g, 11.38 mmol, 1.2 equivalent) were added thereto. Tetrakis(triphenylphosphine)palladium (0.22 g, 0.189 mmol, 0.02 equivalent) was added under nitrogen protection. After the feeding was completed, the reaction flask was transferred to a preheated oil bath pot and reacted at 110° C. for 4 hours. After the reaction was completed, the reaction solution was poured into water, extracted with toluene, the organic phase was washed with water three times, anhydrous sodium sulfate was added to the organic phase, and the crude product was obtained by drying, filtering, and evaporating the solvent under reduced pressure. The crude product was purified by column chromatography, and toluene and n-hexane were selected as eluents, wherein the ratio of toluene to n-hexane was 1:15, and finally a light yellow solid was obtained, which was the ferroelectric nematic liquid crystal molecule ETB095, with a yield of 51.9%. The structural formula of the ferroelectric nematic liquid crystal molecule ETB095 is as follows:
[0114]
[0115] NMR characterization results:
[0116] The hydrogen spectrum is shown in Fig.18 As shown, the results are as follows: 1 H NMR (500 MHz, DMSO) δ 8.45 (m, 4H), 8.21(m, 2H), 8.08 (s, 1H), 7.86 (m, 4H), 7.72(m, 3H), 7.30(m, 4H), 6.95 (m, 2H),3.99 (s, 2H), 1.76 (s, 2H), 1.49 (s, 2H), 1.03 (s, 3H);
[0117] Carbon spectrum Fig.19 As shown, the results are as follows: 13 C NMR (125 MHz, DMSO) δ 165.05, 164.95,156.53, 150.34, 150.11, 144.82, 142.92, 142.42, 139.36, 134.12, 133.83,131.39, 130.50, 130.11, 127.78, 127.71, 127.01, 125.81, 125.71, 125.61,123.57, 122.64, 121.98, 116.86, 67.81, 31.13, 19.20, 13.78;
[0118] Mass spectrometry characterization results:
[0119] ESI (m / z): [M+H] + Calcd. for C 36 H 29 NO7,587.19;found, 588.15.
[0120] Performance test results of ferroelectric nematic liquid crystal molecules:
[0121] (1) Test of thermodynamic properties of ferroelectric nematic liquid crystal molecules:
[0122] Differential scanning calorimetry (DSC) was used to test the thermodynamic properties of ferroelectric nematic liquid crystal molecules. Fig. 20 The phase transition process of the ferroelectric nematic liquid crystal molecule ETA094 at a heating and cooling rate of 10℃ / min is shown. The solid line represents the first cooling curve, and two phase transition peaks appear. When the temperature is at 251℃, it enters the ferroelectric nematic phase from the nematic phase; when the temperature drops to -93℃, it changes from the ferroelectric nematic phase to the crystalline phase, that is, crystallization at -93℃. The dotted line represents the heating curve, and two phase transition peaks also appear, corresponding to the melting point peak and the clearing point peak.
[0123] Fig.21 The figure shows the phase transition process of the ferroelectric nematic liquid crystal molecule ETB095 at a heating and cooling rate of 10℃ / min. The solid line represents the first cooling curve, and two phase transition peaks appear. When the temperature is 249℃, it enters the ferroelectric nematic phase from the nematic phase; when the temperature is -100℃, it enters the ferroelectric nematic phase from the ferroelectric nematic phase, that is, crystallization at -100℃. The dotted line represents the heating curve, and two phase transition peaks also appear, corresponding to the melting point peak and the clearing point peak. In summary, the ferroelectric nematic liquid crystal molecules are inter-convertible thermotropic liquid crystals, and they all have ultra-wide phase transition temperatures.
[0124] (2) Hysteresis loop test of ferroelectric nematic liquid crystal molecules:
[0125] The hysteresis loop is an important basis for proving whether ferroelectric nematic liquid crystal molecules have ferroelectric properties. Fig. 22 and Fig.23 The PE hysteresis loops of the ferroelectric nematic liquid crystal molecules ETA094 and ETB095 at 150°C are shown. The saturation polarization value of the ferroelectric nematic liquid crystal molecule ETA094 reaches 5.5 µC / cm -2 The calculated spontaneous polarization is 3.4 µC / cm -2 The saturation polarization value of the ferroelectric nematic liquid crystal molecule ETB095 reaches 5.5 µC / cm -2The calculated spontaneous polarization is 3.4 µC / cm -2 In summary, the parallelogram hysteresis loop presented by the ferroelectric nematic phase liquid crystal molecules conforms to the properties of general ferroelectric materials, and the saturation polarization value is significant.
[0126] (3) Second harmonic nonlinear optical (SHG) signal measurement:
[0127] In order to prove the existence of ferroelectric nematic phase, the second harmonic nonlinear optical (SHG) signal of ferroelectric nematic phase liquid crystal molecules is measured. The variation of polarization intensity with temperature can be obtained by measuring the intensity change of SHG signal. Fig.24 As shown, SHG signals were detected in the temperature range (-93~251℃) corresponding to the ETA094 ferroelectric nematic phase liquid crystal molecules. Similarly, SHG signals were detected in the temperature range (-100~249℃) corresponding to the ETB095 ferroelectric nematic phase liquid crystal molecules. However, no SHG signals were detected in the temperature range of the non-ferroelectric nematic phase, proving the existence of the ferroelectric nematic phase.
[0128] (4) Thermogravimetric analysis of ferroelectric nematic liquid crystal molecules:
[0129] Thermogravimetric analysis is used to detect the thermal decomposition temperature of ferroelectric nematic liquid crystal molecules. Fig.25 This is the thermogravimetric analysis diagram of ferroelectric nematic liquid crystal molecules ETA094 and ETB095. When the mass loss is 5%, the thermal decomposition temperature of the ferroelectric nematic liquid crystal molecule ETA094 is 330°C, and the thermal decomposition temperature of the ferroelectric nematic liquid crystal molecule ETB095 is 300°C, indicating that the ferroelectric nematic liquid crystal molecules have excellent thermal stability.
[0130] According to the above test results, it can be determined that the ferroelectric nematic liquid crystal molecules provided by this application combine ferroelectricity and liquid crystal properties. While maintaining the high fluidity of liquid crystal, they have a high spontaneous polarization intensity of ferroelectricity, which helps to improve the electric field response speed and dielectric constant of the material, and can have outstanding performance in high-speed electro-optical modulation and efficient photoelectric conversion; the applicable temperature range of the material is expanded, and it can work stably in extreme environments, and is suitable for optoelectronic application scenarios with strict temperature requirements. Therefore, the ferroelectric liquid crystal molecular material shows its broad application prospects in the field of optoelectronic materials, and can be widely used in optoelectronic components such as communication equipment, liquid crystal display units and nonlinear optical elements, to meet the future demand for high-performance materials for optoelectronic devices.
Claims
1. A ferroelectric nematic liquid crystal molecule, characterized in that: The structural formula of the ferroelectric nematic liquid crystal molecule is one of the following structural formulas ETA094 and ETB095: ETA094, ETB095.
2. An application of the ferroelectric nematic liquid crystal molecules as claimed in claim 1, characterized in that: Used in optoelectronic devices.
3. The use of the ferroelectric nematic liquid crystal molecules according to claim 2, characterized in that: The optoelectronic devices include communication equipment, liquid crystal display units and nonlinear optical elements.
Citation Information
Patent Citations
Ferroelectric nematic liquid crystal molecule and preparation method and application thereof
CN118792060A
Cholesteric liquid crystal copolymers and additives
CN1842583A